Bilateral changes of cannabinoid receptor type 2 protein and mRNA in the dorsal root ganglia of a rat neuropathic pain model - Svízenská, Ivana Hradilová; Brázda, Václav; Klusáková, Ilona; Dubový, Petr (The journal of histochemistry and cytochemistry, 2013)
Cannabinoid receptor type 2 (CB2R) plays a critical role in nociception. In contrast to cannabinoid receptor type 1 ligands, CB2R agonists do not produce undesirable central nervous system effects and thus promise to treat neuropathic pain that is often resistant to medical therapy. In the study presented here, we evaluated the bilateral distribution of the CB2R protein and messenger RNA (mRNA) in rat dorsal root ganglia (DRG) after unilateral peripheral nerve injury using immunohistochemistry, western blot, and in situ hybridization analysis. Unilateral chronic constriction injury (CCI) of the sciatic nerve induced neuropathic pain behavior and bilateral elevation of both CB2R protein and mRNA in lumbar L4-L5 as well as cervical C7-C8 DRG when compared with naive animals. CB2R protein and mRNA were increased not only in DRG neurons but also in satellite glial cells. The fact that changes appear bilaterally and (albeit at a lower level) even in the remote cervical DRG can be related to propagation of neuroinflammation alongside the neuraxis and to the neuroprotective effects of CB2R.
Keywords: nervus ischiadicus; Rats, Wistar; spinální ganglia; Ganglia, Spinal; Neuralgia; Rats; Animals; Sciatic Nerve; neuralgie; potkani Wistar; chování zvířat; regulace genové exprese; zvířata; krysa rodu Rattus; Behavior, Animal; Gene Expression Regulation; Receptor, Cannabinoid, CB2; Disease Models, Animal; RNA, Messenger; receptor kanabinoidní CB2; modely nemocí na zvířatech; messenger RNA